Studi Deskripsi SpesifikasiTehnis dari Kamera Mirroless untuk Mengambil Foto Secara Artistik - Rahmad Ferdi Irawan; Deli . (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
The Mirorrless camera is a photographic device used to take pictures through mechanical and electronic processes. It can be interpreted as a combination of technology and art, making photography a complex art and image medium, as well as providing meaning and information. In general, what distinguishes digital SLR cameras from mirrorless cameras is how the image is displayed in the viewfinder. The camera has different composition settings to make it easier to understand each type of photography. In 2009, Olympus introduced a new type of mirrorless camera.